ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT PADA BANK-BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Fitri puji astutik; Dwi Susilowati (Jurnal Ilmu Ekonomi JIE, 2017)
“Analysis of Factors Affecting the demand of Credit at Commercial Banks in Indonesia Stock Exchange Period 2011-2015”.The purpose of this study is to determine the effect by the independent variables of this study, is third-party funds (DPK), operating expenses to operating income (BOPO), Non Performing Loan (NPL), dan gross domestic product (PDB) to demand of credit as variabel dependent. Analysis tool of this research is doubled linear regression using data panel type where data time series as year 2011-2015 and data cross section as 10 commercial banks in indonesia stock excahange. Regression result obtained that variable third-party funds (DPK) have a positive significant effect on demand of credit. Operating expenses to operating income (BOPO) has a negative not significant effect on demand of credit. Non performing loan (NPL) has a negative not significant effect on demand of credit. Gross domestic product (PDB) has a positive significant impact on demand of credit. Coefficient of determination (R2) amount 0.998360 or 99%. That ability of independent variables third-party funds (DPK) (X1), operating expenses to operating income (BOPO) (X2), non performing loan (NPL) (X3), and gross domestic bruto (PDB) (X4). In explaining the dependent variabel of lending is equal to 0.998360 or 99%. While the rest 1% explained by other variabels outside the model. Suggestion in this research is for company can be more optimal in doing credit distribution. And minimize the value of the ratio operating expenses to operating income (BOPO), non performing loan (NPL).Keywords : demand of credit, third-party funds, BOPO, NPL, PDB.